The Correlation between Chronic Periodontitis and Oral Cancer - Maximilian Krüger; Torsten Hansen; Adrian Kasaj; Maximilian Moergel (Case Reports in Dentistry)
Infections are increasingly considered as potential trigger for carcinogenesis apart from risk factors like alcohol and tobacco. The discussion about human papilloma virus (HPV) in oral squamous cell carcinoma (OSCC) points at a general role of infection for the development of oral carcinomas. Furthermore, first studies describe a correlation between chronic periodontitis and OSCC, thus, characterizing chronic inflammation as being a possible trigger for OSCC. In front of this background, we present four well-documented clinical cases. All patients showed a significant anatomical relation between OSCC and clinical signs of chronic periodontitis. The interindividual differences of the clinical findings lead to different theoretical concepts: two with coincidental appearance of OSCC and chronic periodontitis and two with possible de novo development of OSCC triggered by chronic inflammation. We conclude that the activation of different inflammatory cascades by chronic periodontitis negatively affects mucosa and bone. Furthermore, the inflammatory response has the potential to activate carcinogenesis. Apart from a mere coincidental occurrence, two out of four patients give first clinical hints for a model wherein chronic periodontitis represents a potential risk factor for the development of OSCC.